Inflammatory response and bone healing capacity of two porous calcium phosphate ceramics in critical size cortical bone defects. Issue 5 (12th June 2013) - Chatterjea, Anindita; van der, Johan; Danoux, Charlène B.; Yuan, Huipin; Habibovic, Pamela; van, Clemens A.; Weinans, Harrie; de, Jan
Abstract In the present study, two open porous calcium phosphate ceramics, β‐tricalcium phosphate (β‐TCP), and hydroxyapatite (HA) were compared in a critical‐sized femoral defect in rats. Previous comparisons of these two ceramics showed significantly greater osteoinductive potential of β‐TCP upon intramuscular implantation and a better performance in a spinal fusion model in dogs. Results of the current study also showed significantly more bone formation in defects grafted with β‐TCP compared to HA; however, both the ceramics were not capable of increasing bone formation to such extend that it bridges the defect. Furthermore, a more pronounced degradation of β‐TCP was observed as compared to HA. Progression of inflammation and initiation of new bone formation were assessed for both materials at multiple time points by histological and fluorochrome‐based analyses. Until 12 days postimplantation, a strong inflammatory response in absence of new bone formation was observed in both ceramics, without obvious differences between the two materials. Four weeks postimplantation, signs of new bone formation were found in both β‐TCP and HA. At 6 weeks, inflammation had subsided in both ceramics while bone deposition continued. In conclusion, the two ceramics differed in the amount of bone formed after 8 weeks of implantation, whereas no differences were found in the duration of the inflammatory phase after implantation or initiation of new bone formation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1399–1407, 2014.